Pendampingan Ibu-Ibu Rumah Tangga melalui Program Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS) - Risna Podungge; Syam S Kumaji (Univeristas Negeri Gorontalo, 2022)
The KKN-Thematic Village Building Activity Program aims to Assist Housewives Through the Prosperous Family Income Improvement Business Program (UPPKS). The role of mothers as housewives in each family is now not only as taking care of children, washing, etc., but can be worked in helping the head of the household in the welfare of his family through UPPKS (Efforts to Increase Prosperous Family Income). The method used in the KKN-Thematic Village Building program is the assistance to the group of mothers in creating and developing businesses for family welfare. The group of mothers will also be taught knowledge, understanding of resource development that will be the basis in achieving the objectives of the uppks-related programs in Bongo Nol village and Huwongo village. The evaluation is carried out to obtain information not only as learning materials for related mothers but also related to their implementation with the students of KKN Thematic Village Building.The evaluation is carried out to obtain information not only as learning materials for related mothers but also related to their implementation with the students of KKN Thematic Village Building.